Pemanfaatan Pemasaran Digital Berbasis Media Sosial Untuk Meningkatkan Pendapatan UMKM pada Objek Wisata Kuburan Batu Lemo - Rati Pundissing; Theresyam Kabanga; Daud Rodi Palimbong; Rozyana Paulus (Pusat Riset dan Inovasi Nasional, 2026)
The development of digital technology provides significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to increase their marketing reach through social media. However, most MSMEs in the Kuburan Batu Lemo tourist area have not yet optimally utilized social media as a means of business promotion. This community service activity aims to improve MSMEs' understanding and skills in utilizing social media-based digital marketing. The methods used included outreach, training, mentoring, and evaluation through pre- and post-tests. The results of the activity indicate an increase in participants' understanding and skills in using social media as a marketing tool. MSMEs have been able to create business social media accounts, upload promotional content, and reach a wider consumer base. Furthermore, MSMEs have responded positively to the use of social media due to its ease of use and effectiveness in enhancing business promotion. Thus, the use of social media has been proven to enhance MSMEs' digital marketing capacity and has the potential to increase business revenue sustainably.